Soil-Transmitted Helminth Eggs Contamination on Fresh Vegetables in Medan Indonesia - Nurfadly, Nurfadly; Zahara, Iqrina Widia; Nasution, Aisyah Khoiriyah (Universitas Islam Bandung, 2023)
Indonesian people habitually consume fresh vegetables as companions to other foods. We can find soil-transmitted helminths (STH) eggs in fresh vegetables that are not washed clean. This study determines whether there was STH egg contamination in fresh vegetables in several stalls selling fried chicken in Medan. This study was a descriptive study with a cross-sectional design. Research samples were four types of fresh vegetables: lemon basil (Ocimum africanum), lettuce (Lactuca sativa), cucumber (Cucumis sativus), and cabbage (Brassica oleracea var. capitata) collected from 88 fried chicken stalls in Medan in January 2019. All samples were examined by the sedimentation method to ensure STH egg contamination at the Parasitology Laboratory of the Faculty of Medicine Universitas Muhammadiyah Sumatera Utara. The types of fresh vegetables that were most contaminated by STH eggs were lemon basil leaves (Ocimum africanum), and the most abundant STH eggs found were Ascaris lumbricoideseggs. In conclusion, there is egg contamination in fresh vegetables in several stalls selling fried chicken in Medan.